BENEFITTING HIGHER EDUCATION STUDENTS WITH DIGITAL GAMES IN LANGUAGE LEARNING - Pham Thi Thu Hien; Movi Riana Rahmawanti (ENGLISH, 2020)
There has been an abundant raise in recent years in the concern in using digital games for language learning. Additionally, gaming plays an important role in the everyday lives of youngsters and young adults in developed countries. It is a considerable option for teacher to adapt gaming into language learning since gaming itself became a habit that will easily be adopted into learning. This study will examine gaming opportunities in language learning, and how higher education students benefitting from that. It will employ quantitative research that uses Structured Interview and Online Questionnaire as research Instruments. By the end of the study, higher education students found out that digital game is an easy media to implement in language learning due to their familiarity to digital games. The implementation of digital games excites the students in learning English, and makes a conducive learning situation.